Diegetic Biographism: Authorial Intrusions and Interdiscursive Anchorages Producing a Rhetoric of Authenticity in Three Books by Annie Ernaux (ENTHYMEMA, 2017)
After publishing three relatively unnoticed novels, French writer Annie Ernaux stopped labeling her books as novels and adopted a documentary and autobiographical rhetoric. After this autobiographical turn, Ernaux won prestigious prizes and reached a wider audience. This article is an attempt to map out the narrative devices that instigated the impression of urgency, authenticity, and biographical referentiality that the critics praised. Positioning Ernaux’s autobiographical project in relation to the concept of performative biographism, the neologism «diegetic biographism» is proposed for her systematic metanarrative commentary and referential play. Increased reader engagement is thus regarded as a function of Ernaux’s anchoring her narration in an ostensibly biographical reference world.
Keywords: Ernaux; biography; autobiography; authenticity